Parents' Perception of Their Role in Character Education for Early Childhood in Indonesia - Sapta Wati, Eka; Rudianto; Zaman, Badru; Ramdani, Cepi (Universitas Veteran Bangun Nusantara, 2024)
The family serves as the initial gateway for young children to gain various valuable experiences, particularly in understanding character. Cultivating characters that reflect the values of the Indonesian nation is crucial for supporting the government's efforts to produce a golden generation by 2045. This research aims to determine parents' understanding of the family's role in children's character education. The research design is a case study, which explores various information related to parents' understanding in one of the schools in the Bandung area. The research sample consisted of three parents with children aged 3-6 years. The results indicate differences in parents' understanding of their role in early childhood character education. These differences encompass teaching roles, as some parents are not yet aware of effective teaching methods for young children, as well as roles in modeling, motivation, habituation, and rule enforcement. Parents need to learn more about the appropriate role of the family in early childhood character education. By enhancing parents' understanding of character education, there will be a positive impact on the creation of an advanced civilization with a strong national character.